أثر العوامل التكنولوجية والتنظيمية والبيئية على تبني المعاملات الإلكترونية في الشركات الصغيرة والمتوسطة بليبيا – دراسة حالة مدينة رقدالين (Comprehensive Journal of Science, 2026)
This study aimed to analyze the factors influencing the adoption of electronic transactions in small and medium-sized enterprises (SMEs) in the city of Ragdalen, Libya, using the Technology–Organization–Environment (TOE) framework as a theoretical model for explaining organizational adoption of technological innovations. The importance of this study stems from the growing role of electronic transactions in enhancing organizational efficiency and improving business performance in light of the rapid global digital transformation. The study adopted a quantitative research approach by utilizing a structured questionnaire to collect data from a purposive sample of 120 owners and managers of SMEs in Ragdalen. The collected data were analyzed using SPSS software in order to test the study hypotheses related to the impact of technological, organizational, and environmental factors on the adoption of electronic transactions.The statistical analysis revealed that technological and organizational factors have a significant positive impact on the adoption of electronic transactions within SMEs, whereas the environmental factor did not show a statistically significant effect in the applied model. These findings suggest that the adoption of electronic transactions in the Libyan context is largely driven by internal organizational factors, such as managerial support and technological readiness, rather than external environmental pressures. The study concludes that the TOE framework provides a useful lens for understanding digital adoption in SMEs within developing economies; however, the influence of its dimensions may vary depending on the specific institutional and environmental context. Based on these findings, the study recommends strengthening organizational support, investing in technological infrastructure, and developing supportive governmental policies to promote digital transformation and the wider adoption of electronic transactions in the Libyan business environment.
Keywords: Electronic Transactions, SMEs, TOE Framework, Digital Transformation